As-Sulṭatu wa al-Haimanatu as-Siyāsiyatu fi al-Diwān li Ahmad Maṭar (Dirāsah al-Adab al-Ijtimāiy 'inda Antonio Gramsci) - Marisa Salsabila Hamas; Khafid Roziki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study was to determine the ideological formations and the forms of resistance contained in the anthology of Ahmad Mathar's poetry using Hegemony theory based on the perspective of Antonio Gramsci. This research is a descriptive qualitative study. This study used the anthology of Ahmad Mathar's poetry as primary data and used some journals that are relevant to this study as secondary data. Data collection methods were done by reading, listening, and writing. The researchers used persistence, data triangulation, and discussion to test the data validity. The data analysis techniques used the technical analysis version of Miles and Huberman. Data analysis techniques were done by reducing data, presenting data, and concluding. What our study showed were The ideological formations that emerged from 3 main figures in poetry, namely the United States as a political society or the bourgeois class, Saddam Hussein's government as a political and civil society, and Iraq as a civil society. The three figures interpreted several events of hegemony, and each figure has a different ideology. There are three forms of resistance from civil society of hegemony, namely violent resistance from armed groups, humanistic resistance, and ideological negotiation